Poly (alpha-Hydroxy Ester-Urethane) Based Electrospun Biomaterials for Tissue Engineering - (:unkn) unknown (AIDIC SERVIZI SRL, 2013)
Generally fibrous mats are produced via electrospinning and utilized as tissue engineering scaffolds. This technique is widely used in tissue engineering studies due to unique properties of the resulting mats have, such as large surface area-to-volume ratios, high porosity and connected porous structure. In this study, alternatively, novel electrospun non-fibrous surfaces were prepared from poly (alpha-hydroxy ester-urethane) (PU). Low molecular weight alpha-hydroxy ester based polyurethane was synthesized from L-lactide, glycolide and dimethylol propionic acid (DMPA). Biodegradable and biocompatible PUs were then electrospun to obtain non-fibrous surfaces with high porosity and interconnectivity. Collagen blended PU was also prepared for improving cell adhesion and proliferation. 3T3 cells were seeded on electrospun non-fibrous scaffolds. The morphology of novel surfaces was characterized by environmental scanning electron microscope (ESEM). Biocompatibility of the scaffolds was examined by using MTT cytotoxicity assay. According to the results, electrospun scaffolds were non-toxic. 3T3 cells adhered to the electrospun scaffolds and settled into pores in the non-fibrous mesh.
Keywords: GROWTH